Two new species of Trichodrilus (Annelida, Clitellata, Lumbriculidae) from Pacific drainages, western USA - Fend, Steven; Rodriguez, Pilar (Zootaxa, 2024)
Two new species of Lumbriculidae attributed to the mostly-Palearctic genus Trichodrilus Claparède, 1862 are described from Pacific drainages in western North America. Trichodrilus baylesi sp. nov., from Fall Creek (Willamette River drainage, Oregon) has petiolate atria and one pair of spermathecae, in segment XI; it is distinguished from congeners by the spherical atrial ampullae and large, pendant penes in deep sacs. Trichodrilus humptulips , from the Humptulips River (Washington) has paired spermathecae in XI and XII and club-shaped atria, basally joined by thin vasa deferentia which open to the atrial lumen subapically, and without complex penes. The new descriptions increase the confirmed North American Trichodrilus fauna to 4 species, but limited collections from other regions suggest that the North American Trichodrilus fauna is more diverse.